Perception versus intake of fruit and vegetables - Ramos de CARVALHO, Maria Cecília; Carvalho de MENEZES, Mariana; Souza LOPES, Aline Cristine (Revista de Nutrição, 2023)
Objective To compare perception and intake of fruit and vegetables, and to identify the factors associated with misperception of intake. Methods Cross-sectional study with 3,414 participants of the Health Academy Program from Belo Horizonte (MG), Brazil. Stages of change from Transtheoretical Model were used to evaluate perception of intake, and questions adapted from national surveys were used to assess intake of fruit and vegetables as separate groups. Individuals whose intake and perception were discordant were reclassifi ed in pseudo-maintenance (wrongly believe their intake is adequate) or non-refl ective action (wrongly believe their intake is inadequate). Results Insuffi cient intake of fruit and vegetables and misperception of intake were observed. Pseudo-maintenance was more prevalent, given that 45.1% of individuals were reclassifi ed in this stage regarding their vegetable intake and 22.9% regarding fruit. According to multinomial logistic regression, pseudo-maintenance of fruit intakewas associated with sex, schooling, food and nutrition security, weight satisfaction, and participation in nutrition interventions; pseudo-maintenance of vegetable intake was associated with schooling and weight satisfaction. Non-reflective action was associated with age. Conclusion An important discordance between perception and intake was found, with emphasis on pseudo-maintenance of vegetable intake. Misperception was associated with different factors regarding fruit and vegetables, including sociodemographic variables, participation in nutrition interventions, and weight satisfaction. These results can contribute to the design of interventions aligned with eating behavior, aimed to empower individuals for their food choices.